Inactivation of Piscine orthoreovirus. Issue 9 (6th July 2020) - Wessel, Øystein; Hansen, Elisabeth F.; Løvoll, Marie; Inami, Makoto; Husby, Asbjørn; Kruse, Gesa; Dahle, Maria K.; Rimstad, Espen
Abstract: Piscine orthoreovirus infects various salmonid fish species, and the infection is associated with diseases such as heart and skeletal muscle inflammation (HSMI) in farmed Atlantic salmon ( Salmo salar ). There are no vaccines available or genetically selected resistant hosts that can efficiently control piscine orthoreovirus (PRV) infection. Currently, the only prophylactic measure against PRV is general biosecurity measures aiming to break the transmission cycle. Methods to eradicate infectious virus from contaminated facilities are desirable, but the knowledge on how to inactivate PRV is lacking. A major bottleneck for inactivation studies is the lack of ability to propagate PRV in cell culture. Therefore, in this study we developed an in vivo model for detection of infectious PRV particles after treatment of the virus with inactivation tools such as heat, pH, iodine, UV and commercially available disinfectants. The results show that standard iodine treatment is efficient in inactivation of the virus, and similarly are high and low pH extremes and treatment with Virocid, a commercially available disinfectant. A UV dose of at least 50 mJ/cm 2 is required for inactivation, and the virus has high resistance against heat treatment.